Fraud Risk Factors and Audit Programme Modifications: Evidence from Jordan - Modar Abdullatif (Australasian Accounting, Business and Finance Journal, 2013)
This study explores how audit firms in Jordan deal with the presence of fraud risk factors in audit clients. In doing so, the study seeks to explore which fraud risk factors are more important to Jordanian auditors, and how Jordanian auditors consider modifying their audit programmes when fraud risk factors are present in clients. The study uses a structured questionnaire that was administered to senior level auditors in the largest Jordanian audit firms. The findings show that almost all of the 20 fraud risk factors included in the questionnaire were only slightly important (if not unimportant), a finding that is arguably alarming. The perceived importance of modifying the audit programme in the presence of each fraud risk factor was related to the perceived importance of the fraud risk factor itself. However, changes in the nature and extent of audit procedures were more important than changes in the timing of the procedures or the members of the audit team. The most important fraud risk factors were related to the characteristics of management and its attitude towards the audit, while the least important fraud risk factors were related to the difficulties in the client’s financial performance. Factor analysis found that the fraud risk factors could be classified into four separate groups. Possible interpretations of the findings were discussed, such as considering the Jordanian business environment characteristics, and the findings were compared to those of extant international studies.
Keywords: Fraud risk factors; Audit programmes; Audit programs; Audit firms; Jordan